Missionaries of science : the Rockefeller Foundation and Latin America - Cueto, Marcos (Philanthropic studies., 1994)
"Concerns impact of American philanthropy on public health, agriculture, and science in Latin America and relations with State authority from 1920s-60s, with particular attention to Brazil and Mexico"--Handbook of Latin American Studies, v. 57.